Efficacy and safety of antiangiogenic agents or chemotherapy plus EGFR‐TKIs in advanced non‐small cell lung cancer: A systematic review and network meta‐analysis. Issue 6 (2nd January 2023) - Dai, Jiali; Liu, Xinyin; Li, Jun; Qu, Tianyu; Cui, Yanan; Jin, Shidai; Zhang, Erbao; Guo, Renhua
Abstract: Background: The combination of antiangiogenic agents with epidermal growth factor receptor inhibitors (EGFR‐TKIs) and chemotherapy with EGFR‐TKIs are the most common combination treatment options in epidermal growth factor receptor (EGFR) positive non‐small cell lung cancer (NSCLC). This network meta‐analysis was performed to evaluate the differences between them. Methods: We searched the PubMed, EMBASE and the Cochrane Controlled Trials Register up to August 2022. The primary outcomes were progression‐free survival (PFS) and objective response rate (ORR). The secondary endpoints were overall survival (OS), disease control rate (DCR) and adverse events (AEs). The data of hazard ratio (HR) or risk ratio (RR) with their corresponding 95% confidence intervals (CIs) were extracted in the studies. A network meta‐analysis (NMA) was used to indirectly compare the efficacy and safety of antiangiogenic agents plus EGFR‐TKIs and chemotherapy plus EGFR‐TKIs. Results: Pooled data of included studies were demonstrated that chemotherapy plus EGFR‐TKIs had a benefit in ORR compared to antiangiogenic agents plus EGFR‐TKIs in patients with EGFR mutated NSCLC (RR = 1.1, 95% CI: 1.0–1.2). However, there were no significant differences in PFS, OS and DCR between in the two group (PFS: HR = 1.0, 95% CI: 0.74–1.6; OS: HR = 0.78, 95% CI: 0.45–1.5; DCR: RR = 1.0, 95% CI: 0.94–1.1). The common treatment‐related AEs in the two groups were relatively manageable. Conclusion: Based on the efficacy and safety, the combination of chemotherapy with EGFR‐TKIs is considered the best combination treatment options in advanced NSCLC with EGFR mutation. Abstract : Novel findings: Growing evidence demonstrates that EGFR‐TKIs combined with other therapies can significantly alleviate drug resistance and improve the therapeutic effect. For patients with advanced EGFR+ NSCLC, antiangiogenic therapy and chemotherapy are the most common combination therapeutic regimens. Vascular endothelial growth factor inhibits angiogenesis by binding to the vascular endothelial growth factor receptor, which activates proangiogenic signaling. The dual inhibition of the EGFR and VEGF pathway has been proved to significantly enhance antitumor activity in vivo and in vitro. Moreover, the combination of chemotherapy and EGFR‐TKIs provides synergistic antitumor activity by activating extracellular signal‐regulated kinases and promoting apoptosis which may overcome acquired resistance to chemotherapy. Whether antiangiogenic agents plus EGFR‐TKIs or chemotherapy plus EGFR‐TKIs deliver different clinical outcomes remains unknown. Neither option has been studied head‐to‐head in a randomized controlled trial (RCT) to compare the effectiveness and safe. A network meta‐analysis (NMA) was conducted to indirectly compare antiangiogenic therapy plus EGFR‐TKIs versus chemotherapy plus EGFR‐TKIs in advanced EGFR ‐mutated NSCLC. Based on the findings, we were interested in identifying the best choice in advanced EGFR positive NSCLC.